Efficacy and safety of chimeric antigen receptor T-cell in the treatment of hematologic malignancy: an umbrella review of systematic review and meta-analysis - Yu, Zhengyu; Jing, Caixia; Xie, Li; Min, Lang; Li, Lingfeng; Wang, Zhongwang; Niu, Ting (Frontiers in Immunology, 2025)
BackgroundThis umbrella review consolidates data from systematic reviews and meta-analyses on the efficacy and safety of Chimeric Antigen Receptor T-cell (CAR-T) therapy in hematologic malignancies. The aim is to assess CAR-T efficacy across different malignancies, identify key safety concerns, and provide clinical recommendations.MethodsWe conducted a thorough search of PubMed, Embase, Web of Science, and the Cochrane Database of Systematic Reviews up to May 2024. Systematic reviews and meta-analyses evaluating CAR-T efficacy in hematologic malignancies were included. The AMSTAR tool was used to assess methodological quality, and the GRADE system was employed to evaluate the quality of evidence for each outcome.ResultsA total of 105 meta-analyses met the inclusion criteria. CD19-targeted CAR-T therapies demonstrated superior efficacy in acute lymphoblastic leukemia (ALL) and diffuse large B-cell lymphoma (DLBCL), particularly in relapsed or refractory cases (high-quality). However, CAR-T monotherapy showed reduced efficacy in central nervous system lymphoma (CNSL) (middle-quality). Combination therapies, particularly CAR-T with HSCT, improved complete response rates but were associated with increased severe adverse events, such as CRS and neurotoxicity (high-quality). Axi-cel was found to carry a higher risk of ICANS and neutropenia compared to Tisa-ce (high-quality), likely due to its CD28 costimulatory domains, which enhance T-cell activation.ConclusionsCAR-T therapy demonstrates promising clinical outcomes in ALL and DLBCL, but significant safety concerns remain. Combining CAR-T with therapies such as HSCT improves efficacy but also heightens the risk of severe toxicities. Future research should focus on optimizing CAR-T constructs, refining preconditioning regimens, and identifying predictive biomarkers to personalize treatment and mitigate risks in vulnerable populations. Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024581782.